HUMANISING THE CLASSROOM: A PRAGMATIC APPROACH - Nwafor, Naboth H.A.; Nwogu, U. J. (European Scientific Journal, ESJ, 2014)
The formal educational system of any society has specially designated environment for its activities, and that is the classroom where teaching and learning take place. This paper examines what constitutes a humanised classroom environment, what the teacher ought to do to ensure a mutual, friendly classroom climate between the teacher and the student. The paper equally highlighted the outcome of a humanized classroom environment in terms of student’s life style, and achievements, as well as their contributions later in society.